2022
DOI: 10.3390/ma15093259
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Heating Rate during Carbonization on the Porosity, Strength, and Electrical Resistivity of Graphite Blocks Using Phenolic Resin as a Binder

Abstract: In the present study, graphite blocks were fabricated using synthetic graphite scrap and phenolic resin, and the effect of the heating rate during carbonization on their mechanical and electrical characteristics was examined. While varying the heating rate from 1, 3, 5, and 7 to 9 °C/min, the microstructure, density, porosity, flexural strength, compressive strength, and electrical resistivity of the fabricated graphite blocks were measured. As the heating rate increased, the pores in the graphite blocks incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Moisture is released as condensation in the low-temperature range, as CO 2 , CH 4 , and CO in the medium range, and as H 2 in the high range. Gas release occurs rapidly in the medium-temperature range, resulting in the formation of large pores [20,36]. Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moisture is released as condensation in the low-temperature range, as CO 2 , CH 4 , and CO in the medium range, and as H 2 in the high range. Gas release occurs rapidly in the medium-temperature range, resulting in the formation of large pores [20,36]. Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study by our team found that the properties of graphite blocks increased when heating rate during carbonization was adjusted to below 3 • C/min. Graphite blocks prepared at heating rates higher than 5 • C/min had large pores and cracks in their microstructures and exhibited low flexural strength and high electrical resistivity [20].…”
Section: Fabrication Of Graphite Blockmentioning
confidence: 99%
See 3 more Smart Citations